2013
DOI: 10.4172/2157-2518.s14-003
|View full text |Cite
|
Sign up to set email alerts
|

Do Cancer Stem Cells have an Immunomodulatory Role Different from the Bulk of Tumor Cells?

Abstract: Cancer is one of the leading causes of death worldwide. In normal settings, the immune system is responsible for clearing cancer cells from our body. However, many patients develop immune tolerance to tumor cells through upregulation of immune regulatory molecules, release of immune suppressive factors in the tumor microenvironment and/or recruitment of regulatory/suppressive cells that impede the function of other fully activated effector immune cells. In spite of significant progress that have been achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…We previously showed that IGF-1 facilitated immune escape by decreasing the immunogenicity of the murine melanoma B16-F0 cell line [26]. Furthermore, the immunomodulatory properties of tumor cells have recently been linked to EMT and stemness, consistent with a role for CICs in immune escape [15, 5859]. Indeed, ABCB5 + MICs have been shown to induce immune responses less efficiently than the ABCB5 − bulk of the tumor [59].…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that IGF-1 facilitated immune escape by decreasing the immunogenicity of the murine melanoma B16-F0 cell line [26]. Furthermore, the immunomodulatory properties of tumor cells have recently been linked to EMT and stemness, consistent with a role for CICs in immune escape [15, 5859]. Indeed, ABCB5 + MICs have been shown to induce immune responses less efficiently than the ABCB5 − bulk of the tumor [59].…”
Section: Discussionmentioning
confidence: 99%
“…These cancer stem cells, owing to their slow replication, are intrinsically resistant to radiotherapy and are only partially sensitive to chemotherapy [44, 45]. Additionally, the stem cell sub-populations have a strong immune-suppressive effect on the tumor microenvironment [46]. This phenomenon has been captured in our model in the study of the temporal evolution of the tumor-immune interaction dynamics, where we observe that coincident with the proliferation of the stem and resistant stem cell there is also an increased proliferation of the M2 and Treg cells (Fig 2C).…”
Section: Discussionmentioning
confidence: 99%
“…Immune inhibitory molecules like B7-H1 is expressed on tumor cells (tumor infiltrating lymphocytes) and FOXP3+ regulatory T-cells are abundant in the tumor microenvironment in a group of breast cancer patients. Besides, CSCs produce immunosuppressive molecules such as TGF-β, PG E2 and adenosine, or of cytokines such as IL-6 and IL-10, the resistance to apoptosis, and/or the expression of Fas ligand (FasL), which leads to the death of tumor-infiltrating lymphocytes [73]. CSCs would be largely unaffected by standard therapies, because of their stem cell characteristics.…”
Section: Cancer Stem Cells Role In Cancermentioning
confidence: 99%